Use of support services in a sample of patients with high‐risk primary melanomas in urban, regional and rural Queensland - Lena A. von Schuckmann; Bernhard M. Smithers; Kiarash Khosrotehrani; Vanessa L. Beesley; Jolieke C. van der Pols; Maria B. Hughes; Adele C. Green (Australian and New Zealand Journal of Public Health, 2017)
Abstract Objective: To characterise use of support services in patients diagnosed with high‐risk primary melanoma by their location of residence. Methods: In a cross‐sectional study of 787 patients with histologically‐confirmed clinical stage 1B‐2 melanoma, we estimated odds ratios (ORs) using regression models to assess the association of support service use with residence in rural, regional or urban areas. We also evaluated demographic and clinical correlates of support service use. Results: Among 113 rural patients, 33 (29%) used support services around time of diagnosis compared to 88 (39%) of 224 regional participants and 164 of 448 (37%) urban participants. Regional participants more commonly used support services compared to rural participants (OR 1.84; CI 1.09–3.10), but there was no association with urban versus rural residence (OR 1.32; CI 0.82–2.13). As well, females (OR 1.58; CI 1.15–2.18), those <65 years (OR 1.96; CI 1.42–2.71), or with higher education (OR 2.30; CI 1.53–3.44), or those with T‐stage 4B (OR 2.69; CI 1.36–5.32) were more likely to use support services than other patients. Conclusion: Use of support services is lower among rural patients and other sub‐groups of primary melanoma patients who have poorer prognoses than others. Implications for public health: Appropriate triage to support services is required for rural and other vulnerable patient groups to ensure optimal patient care.